High-k HfO2 Based Metal-Oxide-Semiconductor Devices Using Silicon and Silicon Carbide Semiconductor - N.P. Maity; A. Pandey; S. Chakraborty; M. Roy (Журнал нано- та електронної фізики)
In this paper we have calculated the flatband capacitance (CFB) for high-k dielectric material hafnia oxide (HfO2) as an insulator and silicon carbide (SiC) as a semiconductor material for metal-oxide-semiconductor (MOS) devices. We simulate the capacitance-voltage (C-V) characteristics of the MOS devices with ultrathin oxide using ATLAS, a commercially available TCAD tool from SILVACO. The tool has investigated the effect on C-V characteristics of different oxide thickness and doping concentration of SiO2 and HfO2 as insulators and Si and SiC as semiconductor based MOS devices. Excellent agreement was observed over a wide range of oxide thickness and substrate doping for the materials. The C-V characteristics of different polytype of SiC semiconductor also studied for n-type MOS devices.